All Days 2014
DOI: 10.2118/169077-ms
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Miscibility Pressure Studies in the Bakken

Abstract: The Bakken is among the shale reservoirs which have been discovered to hold a vast amount of oil resource contributing to the production boom in the US. This unconventional reservoir, like most others, displays favorable initial production rates due to stimulation by hydraulic fracturing, but production rates quickly decline after few months. Due to the extremely low permeability and low recovery factors, miscible gas injection is considered for improving the recovery of oil in the Bakken formation. Feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 3 publications
4
23
0
Order By: Relevance
“…An equation of state developed for CO 2 injection in a separate study was used in this reservoir model. The predicted minimum miscible pressure (MMP) was 2,500 psi, which is consistent with published MMPs for the Middle Bakken (Adekunle and Hoffman 2014). The equation of state had eight (pseudo-)components and yielded a gas/oil ratio (GOR) of 906 scf/bbl, which is a typical value for the Middle Bakken.…”
Section: Impact On Oil Production When Using the Co 2 -Hybrid Designsupporting
confidence: 82%
See 1 more Smart Citation
“…An equation of state developed for CO 2 injection in a separate study was used in this reservoir model. The predicted minimum miscible pressure (MMP) was 2,500 psi, which is consistent with published MMPs for the Middle Bakken (Adekunle and Hoffman 2014). The equation of state had eight (pseudo-)components and yielded a gas/oil ratio (GOR) of 906 scf/bbl, which is a typical value for the Middle Bakken.…”
Section: Impact On Oil Production When Using the Co 2 -Hybrid Designsupporting
confidence: 82%
“…The simulator couples fluid flow and deformation in 2D DFNs. Fracture elements are allowed to slide or open, and the stresses induced by deformation are calculated by use of the boundary-element method (Crouch and Starfield 1983;Asgian 1989). For more information regarding the fracture simulator, the reader may refer to McClure (2012, 2014), and McClure and Horne (2013.…”
Section: Complex-fracture-propagation Modelingmentioning
confidence: 99%
“…Most gases used for injection include carbon dioxide (CO 2 ), 88 nitrogen (N 2 ), natural gas or the mixture of them. Among these 89 gases, CO 2 has received much more attention for enhanced oil 90 recovery in the Bakken formation [7][8][9]. CO 2 has a considerably 91 lower minimum miscibility pressure (MMP) than that of the other 92 gases such as N 2 and CH 4 [10,11].…”
mentioning
confidence: 99%
“…CO 2 and trapped oil will become completely miscible and 107 CO 2 will extract light and intermediate hydrocarbons from the oil 108 phase, and the interfacial tension will become zero and capillary 109 pressure disappears, resulting in the oil phase and CO 2 phase, 110 which contains some extracted hydrocarbon components, flow 111 together more easily through the porous media [16][17][18]. 112 Fai-Yengo et al [9] presented that the effect of capillary pressure 190 where / is matrix porosity, q s is matrix density, q ' is density of which is defined as 199 199 200 where k is the formation permeability tensor, k r' is the relative per-201 meability of phase, ', p ' is pressure of phase ' and l ' is viscosity of Sigmund correlation [31] is often used to calculate the oil and gas 211 diffusion coefficients (unit is cm 2 /s) since it is valid for both oil 212 and gas phases [32]. The binary diffusion coefficient between com-213 ponent i and j is calculated by [31,32] 214…”
mentioning
confidence: 99%
“…In this state, CO 2 is 10-25% as viscous as water and 70% as dense, facilitating its dispersion into the matrix [9]. CO 2 develops miscibility with the Bakken oil at pressures between 3000 and 3400 psi [10], allowing it to mix with the reservoir fluids and improve their mobility. A study by Song and Yang [11] concluded that recovery performance in tight rocks is ''significantly enhanced'' by cyclical CO 2 injection over traditional waterflooding.…”
Section: Introductionmentioning
confidence: 99%